2011
DOI: 10.1143/apex.4.106502
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Lithography Using Highly Sensitive Negative Type of Plant-Based Resist Material Derived from Biomass on Hardmask Layer

Abstract: We investigated electron beam (EB) lithography using a novel highly sensitive negative type of plant-based resist material derived from biomass on a hardmask layer for trilayer processes. The chemical design concept for using the plant-based resist material with glucose and dextrin derivatives was first demonstrated in the EB lithography. The 1 µm line patterning images with highly efficient crosslinking properties and low film thickness shrinkage were provided under specific process conditions of EB lithograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The thickness of the gas permeable molds was then remeasured. The dissolution rate was determined as the difference between the initial and final thickness of the gas permeable mold layers in the process of manufacturing the gas permeable molds and dipping in the volatile solvent [24][25][26][27]. Figure 6 shows the confocal microscope images of the line and space patterns of the imprinted material patterned by the gas permeable mold.…”
Section: Dissolution Rate Of the Gas Permeable Molds For The Volatilementioning
confidence: 99%
“…The thickness of the gas permeable molds was then remeasured. The dissolution rate was determined as the difference between the initial and final thickness of the gas permeable mold layers in the process of manufacturing the gas permeable molds and dipping in the volatile solvent [24][25][26][27]. Figure 6 shows the confocal microscope images of the line and space patterns of the imprinted material patterned by the gas permeable mold.…”
Section: Dissolution Rate Of the Gas Permeable Molds For The Volatilementioning
confidence: 99%
“…Some researchers went further by replacing the current resists by biosourced polymers soluble in aqueous solutions. Takei et al used derivatives of polysaccharides as negative tone resist for electron beam (e-beam) lithography [6][7][8][9] or for extreme ultra-violet (EUV) lithography 9 whereas Kim et al tested silk as positive and negative tone resists for e-beam 10 or EUV lithography 11 . The polysaccharides of Takei et al were chemically modified with acryloyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…For a few years, biosourced polymers derived from biomass, which are nontoxic, renewable, and biodegradable natural materials, have been studied for water-developable high resolution lithography and have demonstrated their potential on commonly used pattern transfer techniques. [8][9][10][11][12][13][14] Through these studies, it was demonstrated that "green" e-beam lithography can be carried out in an organic-free process with high resolution. Kim et al 11 have produced 30 nm holes spaced of 100 nm with silk as a positive tone resist but did not transfer the features into the sublaying substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of the features into the subjacent layer by CF 4 plasma etching was then realized. [8][9][10]16 However, due to the low selectivity of their saccharide layer to etching conditions, they did use a trilayer stack process: (1) saccharide based e-beam resist (200 nm), (2) a hard mask silicone-based polymer (50 nm), and (3) a thick polymer based etching transfer layer (800 nm). Although the process could be completely done in water, the polymers for the two last layers had to be synthesized.…”
Section: Introductionmentioning
confidence: 99%